Analisis Problematika Penegakkan Hak Asasi Manusia Di Tinjau Dalam Segi Aspek Kemasyarakatan - Fathurrohman Fathurrohman; Hendra Lukito; Ahmad Safrudin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Human rights are rights inherent in every individual universally, without discrimination based on race, religion, gender or other social status. In Indonesia, there have been various cases of human rights violations that have occurred throughout its history. Some of the most famous cases include the 1965 tragedy, mass murder in East Timor, the May 1998 riots, and human rights violations that occurred in Papua and Aceh. At the law enforcement level, Indonesia has established institutions such as the National Human Rights Commission (Komnas HAM) which is responsible for investigating Human Rights (HAM) violations. Law enforcement is a process of applying and implementing the law which aims to maintain order, justice and security in a society. It involves various institutions and individuals responsible for enforcing the law, including police, prosecutors, judges, and other law enforcement agencies. Enforcement of Human Rights (HAM) is indeed limited by Indonesian law. Laws in a country can place limitations on the enforcement of Human Rights (HAM), either explicitly or implicitly. Explicit are rights that can be recognized and explained in legal texts and official documents. Examples include the right to freedom of speech. Implicit are rights that are directly stated in legal texts, but are considered to be implied by broader principles adopted by law, or society. For example, although the right to privacy is not always explicitly stated in some constitutions, this right can be interpreted as an implied right from the rights it recognizes.